2015
DOI: 10.1007/s00167-015-3692-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate cement enhances the torsional strength and stiffness of high tibial osteotomies

Abstract: Injectable calcium phosphate cement improves the initial maximal torsional strength and stiffness of high tibial osteotomy construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A more rigid graft might absorb strains that would have otherwise been transmitted to the hinge. In a cadaveric study, Scordino et al [28] demonstrated that injectable calcium phosphate cement improves the initial maximal torsional strength and stiffness of high tibial osteotomy construct. Schwartz [6] treated their patients suffering from isolated medial knee osteoarthritis secondary to genu varum with a minimally invasive OWHTO using injectable calcium phosphate cement.…”
Section: Discussionmentioning
confidence: 99%
“…A more rigid graft might absorb strains that would have otherwise been transmitted to the hinge. In a cadaveric study, Scordino et al [28] demonstrated that injectable calcium phosphate cement improves the initial maximal torsional strength and stiffness of high tibial osteotomy construct. Schwartz [6] treated their patients suffering from isolated medial knee osteoarthritis secondary to genu varum with a minimally invasive OWHTO using injectable calcium phosphate cement.…”
Section: Discussionmentioning
confidence: 99%